Central Bank Independence, Financial Systems, Political Institutions and Elections in Africa - Agoba, A. (University of Ghana, 2018)
This thesis is related to literature on (i) macroeconomic commitment institutions, i.e. institutions pledging policymakers to pre-established rules and procedures in monetary and fiscal policymaking, in order to overcome the issue of time-inconsistency (ii) institutional economics (iii) the interplay between the effectiveness of commitment and constraints and the institutional framework with focus on Africa where macroeconomic commitment institutions and (iv) political business cycle. Within the framework of establishing the Economic Community of West African States (ECOWAS), Southern African Development Community (SADC), The West African Monetary Union (WAMU) and the Euro-Mediterranean zone, African countries have revised their central bank status, for the purpose of ensuring a much larger autonomy and curbing inflation as a major objective of their monetary policy. The evidence supporting this widespread policy advice, however, is not robust, particularly for developing countries. Many African countries, have been unable to achieve the convergence goals for the Eco which include single digit inflation, fiscal-deficit of not more than 4% of Gross Domestic Product (GDP), and central bank's financing of fiscal deficit not more than 10% of previous year's tax revenue among others. Recent literature suggests that there are conditions under which central bank independence (CBI) is effective. Firstly, the study examines the role of financial development and institutional quality in enhancing the effectiveness of CBI on inflation performance in Africa. It also explores the impact of CBI and elections on fiscal policy and the extent to which institutional quality impacts these relationships. Thirdly, given that price stability is key to growing the financial sector, we investigate the importance of CBI to financial development and the role the quality of political institutions plays in the CBI-financial development nexus. Using recent CBI data from Garriga (2016) on 48 African countries, 90 other developing countries and 40 developed countries over the period 1970-2012, the study finds that while CBI does not have a direct impact on inflation, fiscal policy and financial development in Africa, its effectiveness is enhanced by higher institutional quality. Secondly, the effect of CBI on financial development and the effect of institutional quality on fiscal policy are conditioned on the level of development of the economy. Thirdly, banking sector development enhances the effectiveness of CBI in reducing inflation more than stock market development does in Africa. Furthermore, strong institutions are needed in order to enable central banks control fiscal pressures during election years. While elections directly worsen fiscal performance in Africa, institutional quality enhances CBI's effect on improving fiscal performance in election years across Africa, other developing countries and developed countries. Due to the strong incentives of political authorities to influence economic outcomes in election years, we show that CBI has stronger effects on fiscal performance in election years compared to non-election years, given higher levels of institutional quality in Africa, other developing and developed countries. These findings imply that CBI reforms should be done in tandem with other economic and institutional reforms so as to achieve maximum benefits from the policy. The thesis makes a number of contributions to the existing body of knowledge. Empirically, it is the first single study among other studies on the CBI-inflation nexus, to provide evidence on the ability of both financial development and institutional quality to enhance the effectiveness of central bank independence in achieving price stability in Africa, developing and developed countries. The study is also the first to provide insight on the relative importance of the banking sector and stock markets in enhancing the impact of CBI on inflation in Africa, other developing and developed countries. On the role of institutions in improving fiscal performance, the study is the first to identify that institutional quality's impact is conditional on the level of development of an economy. This study also provides fresh evidence to establish that CBI impacts financial development in Africa and other developing countries given strong political institutions. The study also is first to identify differences in the impact of CBI on fiscal performance in election and non-election years conditioned on institutional quality. Methodologically, the thesis contributes by examining the impact of CBI on net central bank claims on government, a critical channel through which theory identifies CBI to influence fiscal policy. The thesis advances the application of the political business cycle theory by examining if independent central banks behave differently in election versus non-election with regards to influencing fiscal policy. Theoretically, the thesis also advances knowledge in the application of the institutional theory of development by using it to stimulate the effect of political/legal institutions on the effectiveness of monetary institutions in promoting financial development. The thesis offers some recommendations to guide policy formulation. In other to realise and maximise the full benefits of central bank reforms, African central banks should be equipped with human and technical expertise and the financial sector and political/legal framework within which central banks operate, should be developed and improved. This will enhance the credibility of the monetary policy arrangement and the effectiveness of independent central banks through effective monetary policy transmission, respect for central bank laws, and the enforcement of credit limits on central bank financing of government projects. Keywords: Central Bank Independence; Financial Development; Institutional Quality; Monetary Policy; Fiscal Policy
PhD. Finance
Keywords: Central Bank Independence; Financial Development; Institutional Quality; Monetary Policy; Fiscal Policy